To find the zeros of the function \( g(x) = x^{2} - 3x - 10 \), we can factor the quadratic expression.
We look for two numbers that multiply to \(-10\) (the constant term) and add up to \(-3\) (the coefficient of \(x\)).
The two numbers that satisfy these conditions are \(-5\) and \(2\), since:
\[ -5 \times 2 = -10 \quad \text{and} \quad -5 + 2 = -3 \]
Thus, we can factor \( g(x) \) as follows:
\[ g(x) = (x - 5)(x + 2) \]
Now, the zeros of the function occur when \( g(x) = 0 \), which gives us:
\[ (x - 5)(x + 2) = 0 \]
This leads to the following solutions:
\[ x - 5 = 0 \quad \Rightarrow \quad x = 5 \] \[ x + 2 = 0 \quad \Rightarrow \quad x = -2 \]
So, the zeros are \(5\) and \(-2\), and the factors are \((x - 5)\) and \((x + 2)\).
Now looking at your provided statements, the correct statement is:
The zeros are 5 and -2 because the factors are (x-5) and (x+2).